IMPLEMENTASI MEDIA PEMBELAJARAN PICTURE AND PICTURE UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI KESETARAAN NILAI UANG - Masni, Masni; Utami, Amaira (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2023)
Based on the results of initial observations, it is known that the 2nd graders of UPTD SDN 015926 Aek Korsik classified as having lower learning outcomes in mathematics, especially in the material of equivalence in the value of money. Therefore, this research was carried out with the aim of improving student learning outcomes ​​by using Picture and Picture media. This research was carried out through the Classroom Action Research (CAR) method which was divided into two cycles. The research subjects were 15 students of 2nd graders at SDN 015926 Aek Korsik. Based on the research results, the class average score in cycle I was 64.50, namely only 6 students (40.00%) were declared complete and as many as 8 students were declared incomplete. Student learning outcomes increased in cycle II with a classical average value of 75.93 above the class average Success Indicator (IK) score of 70.00. Specifically, there were 14 students (93.30%) who achieved scores above the minimum criteria and were declared complete, and only 1 student was declared incomplete. It can be concluded that the use of Picture and Picture media is able to improve students' mathematics learning outcomes on the subject of equivalence in the value of money.